Embracing a Green Economy: A Roadmap to Sustainable Development - Arya, Kishor (Journal of Advanced Research in Economics and Business Management, 2023)
This article explores the imperative for a paradigm shift towards a Green Economy in response to escalating environmental challenges. Amidst unprecedented material growth, over-exploitation of resources threatens global ecosystems and human survival. The lack of concrete initiatives, particularly from developed nations, amplifies concerns about irreversible environmental damage. The Green Economy, endorsed by global entities such as the World Bank and the International Chamber of Commerce, advocates economic, environmental, and social innovations. Notably, economic transparency, CO2 monitoring, and green technology adoption exemplify key components. Socially inclusive initiatives, like Jaipur Rugs and Braskem, underscore the importance of awareness and employment generation. Additionally, the article introduces the concept of Relative Economics, rooted in ancient Indian wisdom, as a guiding principle towards sustainable development. As the world grapples with the consequences of unchecked growth, the article emphasizes the need for a holistic and collaborative approach to build a resilient and environmentally conscious future.